Mapping heterogeneous polarity in multicompartment nanoparticles. Issue 1 (December 2018) - Palomba, Francesco; Genovese, Damiano; Petrizza, Luca; Rampazzo, Enrico; Zaccheroni, Nelsi; Prodi, Luca
Abstract Understanding polarity gradients inside nanomaterials is essential to capture their potential as nanoreactors, catalysts or in drug delivery applications. We propose here a method to obtain detailed, quantitative information on heterogeneous polarity in multicompartment nanostructures. The method is based on a 2-steps procedure, (i) deconvolution of complex emission spectra of two solvatochromic probes followed by (ii) spectrally resolved analysis of FRET between the same solvatochromic dyes. While the first step yields a list of polarities probed in the nanomaterial suspension, the second step correlates the polarities in space. Colocalization of polarities falling within few nanometer radius is obtained via FRET, a process called here nanopolarity mapping. Here, Prodan and Nile Red are tested to map the polarity of a water-dispersable, multicompartment nanostructure, named PluS nanoparticle (NPs). PluS NPs are uniform core-shell nanoparticles with silica cores (diameter 10 nm) and Pluronic F127 shell (thickness 7 nm). The probes report on a wide range of nanopolarities among which the dyes efficiently exchange energy via FRET, demonstrating the coexistence of a rich variety of environments within nanometer distance. Their use as a FRET couple highlights the proximity of strongly hydrophobic sites and hydrated layers, and quantitatively accounts for the emission component related to external water, which remains unaffected by FRET processes. This method is general and applicable to map nanopolarity in a large variety of nanomaterials.